C-REAKTIVE PROTEIN - Budi Darmanta Sembiring (Universitas Methodist Indonesia, 2021)
CRP which is produced in liver is an acute glycoprotein fase that concentrate will increase at the cell injury infection or inflammation. CRP can be use as predictor to primary risk or the second prevention to the heart disease and as a medical evaluation and has prognostic value. The time of CRP checking becomes important to know how long has been happened the disease risk. The CRP measurement can be done by latex-by-latex Agglutination Assay method, Immunoassay dan High Sensitivity C-Reaktif Protein (hs-CRP).